Confessions of PCICU Leaders: Tales From the Past, Lessons for the Future. (October 2015) - da Cruz, Eduardo M.; Tabbutt, Sarah; Eisenhaur, Mary C.; Jacobs, Jeffrey P.; Graham, Eric M.; Smith, Liz C.; Simsic, Janet; Laussen, Peter C.
Background: The pediatric cardiac intensive care environment is challenging and unpredictable due to the heterogeneous patient population. Leadership within this complex environment is critical for optimal outcomes. Methods: The 10th International Meeting of the Pediatric Cardiac Intensive Care Society provided a forum for leaders to share their own practice and experience that concluded with take-home messages regarding quality, safety, clinical effectiveness, stewardship, and leadership. Results: Presentations defined vital aspects for successful outcomes and highlighted ongoing challenges. Conclusions: Accomplishing exceptional outcomes requires a blend of clinical expertise, leadership, communication skills with briefing and debriefing, meaningful use of data, and transparency among peers and toward patients and their families.